DESIGN OF MANUAL BOOK CAFÉ COFFE ROBUSTA BOAT DEPO KOTA PAGARALAM PALEMBANG - FAUZAN SYANI, Dr. M. Nasrul Kamal, M.Sn., (DEKAVE : Jurnal Desain Komunikasi Visual, 2019)
The purpose of the business guide book Café Coffe Robusta Perahu Depo Resto, based on observations on current conditions, so as not to show a manual book that can be known by the public or consumers, in addition to business competitors Cafe Coffe Robusta Boat Depo Resto that developed in Pagaralam Palembang. The purpose of this design is to create a manual book in the form of logogram and logotype information on Café Coffe Robusta Perahu Depo Resto products.The design method used is the Glass Box method, the design is done rationally and logically, starting from data collection, interviews and observation. The analytical approach used is the 5W + 1H analysis method (what, who, where, when, why, how) to find a solution to the problem at hand.The results of the design of the main media Café Coffe Robusta Perahu Depo Resto are manual books, as well as supporting media namely, sign boards, menu lists, clothes, aprons, posters, x-banners, mugs, stickers, pins, which aim to strengthen the application of the main media.Keywords : Manual Book, Brand, and Café Coffe Robusta Perahu Depo Resto.